The Spectrum of Movement Disorders in Childhood‐onset Lysosomal Storage Diseases - Ebrahimi‐Fakhari, Darius (Mov Disord Clin Pract, 2018)
BACKGROUND: Movement disorders are a significant clinical problem in lysosomal storage diseases (LSD) and account for substantial morbidity. The spectrum of movement disorders in childhood‐onset LSD, however, remains poorly defined. OBJECTIVES: To define the spectrum of movement disorders in a well‐characterized cohort of children with LSD. METHODS: A retrospective chart review at a single tertiary care center (Boston Children's Hospital). Patients up to the age of 18 years with a clinical, genetic, and/or biochemical diagnosis of an LSD and at least one predefined movement disorder (parkinsonism, dystonia, ataxia, tremor, chorea, myoclonus, ballism, restless leg syndrome) were included. RESULTS: Ninety‐six patients were identified and 76 patients had a sufficiently document biochemical and/or genetic diagnosis. Of these, 18 patients met inclusion criteria (mean age: 10.3 ± 5.8 [SD] years, range: 3–18 years; 72% male). The most common LSD associated with a movement disorder was Niemann‐Pick disease type C (NPC), followed by several types of neuronal ceroid lipofuscinosis (NCL), and different mucopolysaccharidoses. The most common movement disorder was ataxia followed by rest tremor, dystonia, and myoclonus. The other predefined movement disorders were rare. The majority of patients presented with more than one movement disorder. The movement disorder was slowly progressive in all patients. Brain MRI changes included diffuse cerebral volume loss, white matter abnormalities with thinning of the corpus callosum, and cerebellar atrophy. CONCLUSIONS: Movement disorders develop in a significant number of LSD patients. Ataxia, often in patients with NPC and NCL, is the most common phenotype but significant heterogeneity exists within and between different LSD.